Problems in Adoption of Scientific Fish Farming in Selected Districts of North Eastern India - Dutta, Manas Pratim; Hussain, Shah Mustahid; Mishra, B P (Indian Journal of Extension Education, 2020)
The study was carried out on 120 fish farmers in Nagaon district of Assam and East Siang District of Arunachal Pradesh focusing on the bottlenecks in adoption of scientific fish farming practices. For collection of responses from the respondents about problems of scientific fish farming and related information, a structured questionnaire comprising of 17 factors was designed based on the preliminary survey and focus group discussion was personally administered during the personal interview. Constraint index (CI) was developed and used to measure and compare the constraints expressed by different respondents and the factors were thus ranked on the basisÂ of fish farmers’ perception in the studied area. The adoption level of scientific fish farming depending on theirÂ age group were also studied and 63.33 per cent respondent belong to the medium category age group.